Peran Notaris Dalam Penyuluhan Hukum Tentang KITAS Berkaitan Dengan Hak Atas Tanah Orang Asing - Tirtayasa, I Gede; Sarjana, I Made (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 01 (2024)DO - 10.24843/AC.2024.v09.i01.p12, 2024)
The purpose of this article is to understand the provisions for obtaining usage rights for foreigners and the role of notaries in providing legal education regarding the legal consequences that could occur on usage rights if foreigners fail to extend their KITAS. This research is Normative legal research using a Conceptual Approach and a statute Approach. Based on the research carried out, it was found that the basic requirement that foreigners who want to own a residence in Indonesia with a right to use is to have immigration documents in accordance with the applicable regulations, one of which can be a KITAS. Notaries have the authority to provide legal counseling regarding the deeds they make have an important role in providing outreach to foreigners regarding the requirements and obligations that must be fulfilled as subjects of use rights holders to orderly extend their KITAS.